Nanofiber / graphite felt composite electrode material for flow battery and preparation method of nanofiber / graphite felt composite electrode material
By growing silicon carbide nanowires or carbon nanotubes on the surface of carbon fiber graphite felt and performing water vapor activation, the problems of poor hydrophilicity, insufficient active sites and small specific surface area of carbon fiber graphite felt electrode materials are solved, significantly improving the liquid flow Electrochemical properties of batteries.
Patent Information
- Application Number
- CN202411408526.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The carbon fiber graphite felt electrode material has problems such as poor hydrophilicity, insufficient active sites and small specific surface area, which limits the energy storage performance of the flow battery.
By growing silicon carbide nanowires or carbon nanotubes on the surface of carbon fiber graphite felt and performing water vapor activation, its specific surface area, hydrophilicity and electrical conductivity are enhanced.
It improves the electrochemical performance of the flow battery, enhances the hydrophilicity and conductivity of the electrode, and solves the problem of insufficient energy storage performance of the electrode material.
Smart Images

Figure BDA0005077354650000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of liquid flow battery energy storage, and in particular to a nanofiber / graphite felt composite electrode material for a liquid flow battery and a preparation method thereof. Background Art
[0002] The electrode materials of all-vanadium flow batteries can be divided into metal electrode materials and carbon electrode materials according to the material type. At present, polyacrylonitrile-based carbon felt and graphite felt have high porosity and mechanical strength, good conductivity and acid and alkali corrosion resistance and other excellent properties among the electrode materials of all-vanadium flow batteries. They are the most widely used carbon electrode materials. However, they still have problems such as poor hydrophilicity, insufficient active sites and small specific surface area, which limit the energy storage performance of the battery. At present, the research is to modify the graphite felt electrode by means of functional group modification, heteroatom doping and etching. Although the electrocatalytic performance of the electrode for the redox reaction of metal ions is enhanced, most methods have problems such as complex process, high cost and inability to be industrialized or uneven modification. The diameter of nanofibers is between 1nm and 1000nm, and its physical and chemical properties will change. It mainly has the characteristics of surface effect, small size effect, quantum size effect, macroscopic quantum positive tunneling effect, etc. Loading it on the surface of carbon fiber graphite felt can further increase the specific surface area, hydrophilicity and conductivity, thereby further improving the electrochemical performance of the flow battery.
[0003] Therefore, there is an urgent need to provide a nanofiber / graphite felt composite electrode material for a liquid flow battery and a preparation method thereof to solve the above-mentioned problems of the carbon fiber graphite felt electrode material. Summary of the invention
[0004] Based on the above, the purpose of the present invention is to provide a nanofiber / graphite felt composite electrode material for liquid flow batteries and a preparation method thereof, so as to solve the problems of poor hydrophilicity, insufficient active sites and small specific surface area of carbon fiber graphite felt electrode materials, while improving the electrochemical performance of liquid flow batteries.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a nanofiber / graphite felt composite electrode material for a flow battery comprises the following steps:
[0007] The carbon fiber graphite felt is soaked in a nickel nitrate catalyst solution and then dried for standby use, and a vacuum thermal evaporation method is used to use silicon powder and silicon dioxide powder as silicon sources to grow silicon carbide nanowires on the surface of the dried carbon fiber graphite felt to prepare a silicon carbide nanowire / graphite felt composite electrode material; or
[0008] The carbon fiber graphite felt is soaked in an iron nitrate-anhydrous ethanol solution and then dried for standby use, and a floating catalyst chemical vapor deposition method is used, with ferrocene as a catalyst precursor, cyclohexane as a solvent and a reaction carbon source, and thiophene as an additive, so that carbon nanotubes grow on the surface of the dried carbon fiber graphite felt, thereby preparing a carbon nanotube / graphite felt composite electrode material;
[0009] The silicon carbide nanowire / graphite felt composite electrode material or the carbon nanotube / graphite felt composite electrode material is activated with water vapor in an activation furnace to prepare a modified nanofiber / graphite felt composite electrode material for a liquid flow battery.
[0010] As a preferred embodiment of a method for preparing a nanofiber / graphite felt composite electrode material for a liquid flow battery, the diameter of the carbon fiber graphite felt is 2.5-6 mm.
[0011] As a preferred embodiment of a method for preparing a nanofiber / graphite felt composite electrode material for a liquid flow battery, the porosity of the carbon fiber graphite felt is 65%-90%, and the heat treatment temperature of the carbon fiber graphite felt is 2200°C-2800°C.
[0012] As a preferred embodiment of the method for preparing a nanofiber / graphite felt composite electrode material for a liquid flow battery, the mass ratio of the silicon powder to the silicon dioxide powder is (1-1.5): (0.5-1).
[0013] As a preferred embodiment of a method for preparing a nanofiber / graphite felt composite electrode material for a liquid flow battery, the reaction temperature of the vacuum thermal evaporation method is 1250° C.-1400° C., and the reaction time is 15-60 min.
[0014] As a preferred embodiment of the method for preparing a nanofiber / graphite felt composite electrode material for a liquid flow battery, the concentration of the ferric nitrate solution is 0.025-0.1 mol / L.
[0015] As a preferred embodiment of the method for preparing a nanofiber / graphite felt composite electrode material for a liquid flow battery, the mass ratio of the ferrocene, the cyclohexane, and the thiophene is 1:(0.2-0.6):(0.05-0.1); the concentration of the ferrocene is not higher than 10 g / L, and the volume fraction of the thiophene is not higher than 0.2 vol%.
[0016] As a preferred embodiment of a method for preparing a nanofiber / graphite felt composite electrode material for a liquid flow battery, the reaction temperature of the floating catalyst chemical vapor deposition method is 800°C-1000°C.
[0017] As a preferred embodiment of the method for preparing a nanofiber / graphite felt composite electrode material for a liquid flow battery, the reaction temperature of the water vapor activation process is 750-900° C., and the reaction time is 1-5 hours.
[0018] A nanofiber / graphite felt composite electrode material for a liquid flow battery is prepared by any one of the preparation methods described above.
[0019] The beneficial effects of the present invention are:
[0020] The present invention provides a nanofiber / graphite felt composite electrode material for liquid flow battery and a preparation method thereof, wherein silicon carbide nanowires or carbon nanotubes are loaded on carbon fiber graphite felt to make it have good micropores, large capillary force, and increase hydrophilicity, and silicon carbide nanowires or carbon nanotubes can also be used to construct a three-dimensional conductive and thermal network in the graphite felt system to increase thermal conductivity and electrical conductivity, and then the nanofiber / graphite felt composite material is water vapor activated to load various types of oxygen functional groups, which can also increase its hydrophilicity, and finally obtain a high-performance nanofiber / graphite felt composite electrode material. In addition, nanofibers are loaded on carbon fiber graphite felt, which has the characteristics of surface effect, small size effect, and quantum size effect, and further improves the specific surface area and electrical conductivity of carbon fiber graphite felt. Therefore, the nanofiber / graphite felt composite electrode material prepared in this application has excellent specific surface area, hydrophilicity and electrical conductivity, can be used in liquid flow battery energy storage system, and has high electrochemical performance. DETAILED DESCRIPTION
[0021] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.
[0022] In this embodiment, the present invention provides a method for preparing a nanofiber / graphite felt composite electrode material for a flow battery, comprising the following steps:
[0023] S100, soaking the carbon fiber graphite felt in a nickel nitrate catalyst solution and drying it for standby use, using a vacuum thermal evaporation method, using silicon powder and silicon dioxide powder as silicon sources, so that silicon carbide nanowires grow on the surface of the dried carbon fiber graphite felt, and preparing a silicon carbide nanowire / graphite felt composite electrode material;
[0024] Specifically, the diameter of the carbon fiber graphite felt is 2.5-6mm, and the diameter of the carbon fiber graphite felt can be specifically set to 2.5mm, 4mm or 6mm; the porosity of the carbon fiber graphite felt is 65%-90%, and the heat treatment temperature of the carbon fiber graphite felt is 2200℃-2800℃.
[0025] Specifically, the mass ratio of silicon powder to silicon dioxide powder is (1-1.5): (0.5-1); the reaction temperature of the vacuum thermal evaporation method is 1250° C.-1400° C., and the reaction time is 15-60 min.
[0026] S200, activating the silicon carbide nanowire / graphite felt composite electrode material with water vapor in an activation furnace to prepare a modified nanofiber / graphite felt composite electrode material for a liquid flow battery.
[0027] Specifically, the reaction temperature of the steam activation process is 750-900° C., and the reaction time is 1-5 hours.
[0028] In another embodiment, the present invention also provides a method for preparing a nanofiber / graphite felt composite electrode material for a flow battery, comprising the following steps:
[0029] S100, soaking the carbon fiber graphite felt in an iron nitrate-anhydrous ethanol solution and drying it for standby use, using a floating catalyst chemical vapor deposition method, with ferrocene as a catalyst precursor, cyclohexane as a solvent and a reaction carbon source, and thiophene as an additive, so that carbon nanotubes grow on the surface of the dried carbon fiber graphite felt, and preparing a carbon nanotube / graphite felt composite electrode material.
[0030] Specifically, the diameter of the carbon fiber graphite felt is 2.5-6mm, and the diameter of the carbon fiber graphite felt can be specifically set to 2.5mm, 4mm or 6mm; the porosity of the carbon fiber graphite felt is 65%-90%, and the heat treatment temperature of the carbon fiber graphite felt is 2200℃-2800℃.
[0031] Specifically, the concentration of the ferric nitrate solution is 0.025-0.1 mol / L; the mass ratio of ferrocene, cyclohexane and thiophene is 1:(0.2-0.6):(0.05-0.1); the concentration of ferrocene is not higher than 10 g / L, and the volume fraction of thiophene is not higher than 0.2 vol%; the reaction temperature of the floating catalyst chemical vapor deposition method is 800°C-1000°C.
[0032] S200, activating the carbon nanotube / graphite felt composite electrode material with water vapor in an activation furnace to prepare a modified nanofiber / graphite felt composite electrode material for a liquid flow battery.
[0033] Specifically, the reaction temperature of the steam activation process is 750-900° C., and the reaction time is 1-5 hours.
[0034] The present invention will be further described below by means of specific examples.
[0035] Example 1
[0036] 2.5 mm carbon fiber graphite felt was soaked in a nickel nitrate catalyst solution and then dried for standby use. Silicon carbide nanowires were grown on the surface of the dried carbon fiber graphite felt using a vacuum thermal evaporation method and silicon powder and silicon dioxide powder as silicon sources, wherein the mass ratio of silicon powder to silicon dioxide powder was 1:1, the vacuum thermal evaporation temperature was 1300°C, and the insulation time was 60 min, to obtain a silicon carbide nanowire / graphite felt composite electrode material;
[0037] The silicon carbide nanowire / graphite felt composite electrode material is activated by water vapor at an activation temperature of 850° C. for an activation time of 2 h to obtain an activated silicon carbide nanowire / graphite felt composite electrode material, which is collectively referred to as a nanofiber / graphite felt composite electrode material for a liquid flow battery;
[0038] The above-mentioned nanofiber / graphite felt composite electrode material was placed in a single cell testing device for all-vanadium liquid flow battery to carry out electrochemical performance testing.
[0039] Example 2
[0040] 4mm carbon fiber graphite felt was soaked in nickel nitrate catalyst solution and then dried for standby use. Silicon carbide nanowires were grown on the surface of the dried carbon fiber graphite felt using vacuum thermal evaporation method and silicon powder and silicon dioxide powder as silicon sources, wherein the mass ratio of silicon powder to silicon dioxide powder was 1.5:0.5, the vacuum thermal evaporation temperature was 1250°C, and the insulation time was 15 min, to obtain a silicon carbide nanowire / graphite felt composite electrode material;
[0041] The silicon carbide nanowire / graphite felt composite electrode material is activated by water vapor at an activation temperature of 750° C. and an activation time of 5 h to obtain an activated silicon carbide nanowire / graphite felt composite electrode material, which is collectively referred to as a nanofiber / graphite felt composite electrode material for a liquid flow battery;
[0042] The above-mentioned nanofiber / graphite felt composite electrode material was placed in a single cell testing device for all-vanadium liquid flow battery to carry out electrochemical performance testing.
[0043] Example 3
[0044] 6mm carbon fiber graphite felt was soaked in nickel nitrate catalyst solution and dried for standby use. Silicon carbide nanowires were grown on the surface of the dried carbon fiber graphite felt using vacuum thermal evaporation method and silicon powder and silicon dioxide powder as silicon sources, wherein the mass ratio of silicon powder to silicon dioxide powder was 1:0.5, the vacuum thermal evaporation temperature was 1400°C, and the insulation time was 40 minutes to obtain silicon carbide nanowire / graphite felt composite electrode material;
[0045] The silicon carbide nanowire / graphite felt composite electrode material is activated by water vapor at an activation temperature of 900° C. for an activation time of 1 h to obtain an activated silicon carbide nanowire / graphite felt composite electrode material, which is collectively referred to as a nanofiber / graphite felt composite electrode material for a liquid flow battery;
[0046] The above-mentioned nanofiber / graphite felt composite electrode material was placed in a single cell testing device for all-vanadium liquid flow battery to carry out electrochemical performance testing.
[0047] Example 4
[0048] 2.5 mm carbon fiber graphite felt is soaked in an iron nitrate-anhydrous ethanol solution and then dried for standby use, and a floating catalyst chemical vapor deposition method is used, ferrocene is used as a catalyst precursor, cyclohexane is used as a solvent and a reaction carbon source, and thiophene is used as an additive, so that carbon nanotubes grow on the surface of the dried carbon fiber graphite felt, wherein the concentration of the iron nitrate solution is 0.025 mol / L, the reaction temperature of the floating catalyst chemical vapor deposition method is 800° C., the mass ratio of ferrocene, cyclohexane, and thiophene is 1:0.2:0.05, the concentration of ferrocene is 5 g / L, and the volume fraction of thiophene is 0.2 vol%, to obtain a carbon nanotube / graphite felt composite electrode material;
[0049] The carbon nanotube / graphite felt composite electrode material is activated by water vapor at an activation temperature of 850° C. and an activation time of 2 h to obtain an activated carbon nanotube / graphite felt composite electrode material, which is collectively referred to as a nanofiber / graphite felt composite electrode material for a liquid flow battery;
[0050] The above-mentioned nanofiber / graphite felt composite electrode material was placed in a single cell testing device for all-vanadium liquid flow battery to carry out electrochemical performance testing.
[0051] Example 5
[0052] 4 mm carbon fiber graphite felt is soaked in an iron nitrate-anhydrous ethanol solution and then dried for standby use, and a floating catalyst chemical vapor deposition method is used, ferrocene is used as a catalyst precursor, cyclohexane is used as a solvent and a reaction carbon source, and thiophene is used as an additive, so that carbon nanotubes grow on the surface of the dried carbon fiber graphite felt, wherein the concentration of the iron nitrate solution is 0.05 mol / L, the reaction temperature of the floating catalyst chemical vapor deposition method is 900° C., the mass ratio of ferrocene, cyclohexane, and thiophene is 1:0.6:0.1, the concentration of ferrocene is 8 g / L, and the volume fraction of thiophene is 0.1 vol%, to obtain a carbon nanotube / graphite felt composite electrode material;
[0053] The carbon nanotube / graphite felt composite electrode material is activated by water vapor at an activation temperature of 750° C. for an activation time of 5 h to obtain an activated carbon nanotube / graphite felt composite electrode material, which is collectively referred to as a nanofiber / graphite felt composite electrode material for a liquid flow battery;
[0054] The above-mentioned nanofiber / graphite felt composite electrode material was placed in a single cell testing device for all-vanadium liquid flow battery to carry out electrochemical performance testing.
[0055] Example 6
[0056] 6mm carbon fiber graphite felt is soaked in an iron nitrate-anhydrous ethanol solution and then dried for standby use, and a floating catalyst chemical vapor deposition method is used, ferrocene is used as a catalyst precursor, cyclohexane is used as a solvent and a reaction carbon source, and thiophene is used as an additive, so that carbon nanotubes grow on the surface of the dried carbon fiber graphite felt, wherein the concentration of the iron nitrate solution is 0.1 mol / L, the reaction temperature of the floating catalyst chemical vapor deposition method is 1000°C, the mass ratio of ferrocene, cyclohexane, and thiophene is 1:0.2:0.05 (in other embodiments, the mass ratio of ferrocene, cyclohexane, and thiophene can also be set to 1:0.6:0.05), the concentration of ferrocene is 10 g / L, and the volume fraction of thiophene is 0.05 vol%, to obtain a carbon nanotube / graphite felt composite electrode material;
[0057] The carbon nanotube / graphite felt composite electrode material is activated by water vapor at an activation temperature of 900° C. for an activation time of 1 h to obtain an activated carbon nanotube / graphite felt composite electrode material, which is collectively referred to as a nanofiber / graphite felt composite electrode material for a liquid flow battery;
[0058] The above-mentioned nanofiber / graphite felt composite electrode material was placed in a single cell testing device for all-vanadium liquid flow battery to carry out electrochemical performance testing.
[0059] In order to further illustrate the key points of this patent, a comparative case is added for illustration.
[0060] Comparative Example 1
[0061] The 2.5 mm carbon fiber graphite felt was activated by water vapor at an activation temperature of 850°C for an activation time of 2 h to obtain the activated carbon fiber graphite felt, which can be used as an electrode material and placed in a single cell test device for all-vanadium liquid flow battery testing for electrochemical performance testing.
[0062] The electrode materials prepared in the examples and comparative examples were subjected to electrochemical performance tests. The performance and electrochemical properties (current density 80 mA / cm 2 ) are shown in Table 1.
[0063] Table 1 Electrochemical test results
[0064]
[0065] From the above test results, it can be obtained that the volume density and porosity of the embodiment and the comparative example are not much different, indicating that the modification of silicon carbide nanowires and carbon nanotubes has little effect on the volume density and porosity of carbon fiber graphite felt. At the same time, the nanofiber / graphite felt composite electrode material for liquid flow battery prepared in this application has excellent specific surface area and energy efficiency, and can be used in liquid flow battery energy storage systems.
[0066] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.
Claims
1. A method for preparing a nanofiber / graphite felt composite electrode material for a flow battery, characterized in that: The following steps are involved: The carbon fiber graphite felt is soaked in a nickel nitrate catalyst solution and then dried for standby use, and a vacuum thermal evaporation method is used to use silicon powder and silicon dioxide powder as silicon sources to grow silicon carbide nanowires on the surface of the dried carbon fiber graphite felt to prepare a silicon carbide nanowire / graphite felt composite electrode material; or The carbon fiber graphite felt is soaked in an iron nitrate-anhydrous ethanol solution and then dried for standby use, and a floating catalyst chemical vapor deposition method is used, with ferrocene as a catalyst precursor, cyclohexane as a solvent and a reaction carbon source, and thiophene as an additive, so that carbon nanotubes grow on the surface of the dried carbon fiber graphite felt, thereby preparing a carbon nanotube / graphite felt composite electrode material; The silicon carbide nanowire / graphite felt composite electrode material or the carbon nanotube / graphite felt composite electrode material is activated with water vapor in an activation furnace to prepare a modified nanofiber / graphite felt composite electrode material for a liquid flow battery.
2. The method for preparing the nanofiber / graphite felt composite electrode material for liquid flow battery according to claim 1, characterized in that: The diameter of the carbon fiber graphite felt is 2.5-6 mm.
3. The method for preparing a nanofiber / graphite felt composite electrode material for a flow battery according to claim 1, characterized in that: The porosity of the carbon fiber graphite felt is 65%-90%, and the heat treatment temperature of the carbon fiber graphite felt is 2200°C-2800°C.
4. The method for preparing a nanofiber / graphite felt composite electrode material for a flow battery according to claim 1, characterized in that: The mass ratio of the silicon powder to the silicon dioxide powder is (1-1.5):(0.5-1).
5. The method for preparing a nanofiber / graphite felt composite electrode material for a flow battery according to claim 1, characterized in that: The reaction temperature of the vacuum thermal evaporation method is 1250° C.-1400° C., and the reaction time is 15-60 min.
6. The method for preparing a nanofiber / graphite felt composite electrode material for a flow battery according to claim 1, characterized in that: The concentration of the ferric nitrate solution is 0.025-0.1 mol / L.
7. The method for preparing a nanofiber / graphite felt composite electrode material for a liquid flow battery according to claim 1, characterized in that: The mass ratio of the ferrocene, the cyclohexane and the thiophene is 1:(0.2-0.6):(0.05-0.1); the concentration of the ferrocene is not higher than 10 g / L, and the volume fraction of the thiophene is not higher than 0.2 vol%.
8. The method for preparing a nanofiber / graphite felt composite electrode material for a liquid flow battery according to claim 1, characterized in that: The reaction temperature of the floating catalyst chemical vapor deposition method is 800°C-1000°C.
9. The method for preparing a nanofiber / graphite felt composite electrode material for a flow battery according to claim 1, characterized in that: The reaction temperature of the steam activation process is 750-900° C., and the reaction time is 1-5 hours.
10. A nanofiber / graphite felt composite electrode material for a liquid flow battery, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carbon material surface silicon carbide nanowhiskers and preparation method thereof
CN106784667A
Preparation method of self-supported carbide-derived carbon nanowire
CN107128926A
A method for constructing seed tree effect of high specific surface carbon fiber mat and application thereof
CN109216710A
Preparation method of carbon felt for redox flow battery
CN115881981A
Electrode for electrochemical use, and method for manufacturing said electrode
WO2017071966A1
Cited By
Fiber electrode and preparation method thereof
CN120998925A
Preparation method of carbon-carbon composite fiber material
CN121575584A